2015
DOI: 10.1063/1.4907734
|View full text |Cite
|
Sign up to set email alerts
|

Lifshitz metal–insulator transition induced by the all-in/all-out magnetic order in the pyrochlore oxide Cd2Os2O7

Abstract: We investigate the metal-insulator transition (MIT) of the osmium pyrochlore oxide Cd 2 Os 2 O 7 through transport and magnetization measurements. The MIT and a magnetic transition to the all-in/all-out (AIAO) order occur simultaneously at 227 K. We propose a mechanism based on a Lifshitz transition induced by the AIAO magnetic order probably via strong spin-orbit couplings in the specific semimetallic band structure. It is suggested, moreover, that two observed puzzles, a finite conductivity near T = 0 and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 40 publications
7
43
0
Order By: Relevance
“…Similar conducting MDWs have also been suggested in Cd 2 Os 2 O 7 1017. Interestingly, weak ferromagnetism is observed below T N in both compounds1011; the origin remains unclear and we speculate it related to the MDWs.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Similar conducting MDWs have also been suggested in Cd 2 Os 2 O 7 1017. Interestingly, weak ferromagnetism is observed below T N in both compounds1011; the origin remains unclear and we speculate it related to the MDWs.…”
supporting
confidence: 81%
“…On the other hand, microwave impedance microscopy successfully visualized the MDWs of Nd 2 Ir 2 O 7 , which indicates that the MDWs remain conducting even when the domains themselves become insulating1516. Similar conducting MDWs have also been suggested in Cd 2 Os 2 O 7 1017. Interestingly, weak ferromagnetism is observed below T N in both compounds1011; the origin remains unclear and we speculate it related to the MDWs.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…We fixed T ¼ 200 K as we focused on a narrow T region from 180 to 219 K. For simplicity, we assumed that both the valance and conduction bands were 3D parabolic with the same m, although previous Hall measurements revealed that m of electrons is slightly smaller than that of holes [34]. We found that calculations without these assumptions gave similar results [31].…”
Section: Fig 1 (Color Online) (A)supporting
confidence: 66%
“…Notably these MITs do not appear to be associated with any spontaneous structural symmetry breaking, placing them outside of the aforementioned Mott-Hubbard paradigm. Examples include some of the 5d 5 pyrochlore iridates R 2 Ir 2 O 7 (R = Ln 3+ ) [8,9], plus the 5d 3 osmates Cd 2 Os 2 O 7 [10][11][12][13] and NaOsO 3 . Various mechanisms have been proposed to describe these MITs, notably the Lifshitz and Slater mechanisms.…”
Section: Introductionmentioning
confidence: 99%